Systematic Literature Review: Models and Indicators for Measuring Organizational Performance in the Digital Era - Fatmasari Endayani; Sudarmiatin Sudarmiatin; Agus Hermawan (Digital Innovation : International Journal of Management, 2025)
Digital transformation has changed the way modern organizations measure their success, but traditional performance measurement models have not fully adapted to the needs of the digital age. This study conducted a systematic literature review of 25 high-quality publications from the Scopus, Web of Science, and Emerald Insight databases to identify models and indicators of organizational performance measurement in the digital era. Using the PRISMA 2020 framework and strict inclusion-exclusion protocols, this study analyzes research from the period 2021-2025 with a focus on the integration of the digital dimension in the performance measurement framework. Key findings identify 13 categories of key indicators that consistently appear in the literature, including financial performance, operational efficiency, innovation performance, digital transformation readiness, customer experience, and employee digital capability. The analysis of influence mechanisms found three ways in which digital transformation affects performance: direct effects, mediating effects through dynamic capability and organizational agility, and moderation effects from contextual and organizational cultural factors. The research proposes a three-level integrative framework (strategic, operational, and individual-cultural) that can be differentially adapted according to the size of the organization and the industry sector. The theoretical contribution of this research enriches the academic literature with a systematic synthesis of digital performance measurement, while practical contribution provides evidence-based guidance for organizations in designing a comprehensive performance measurement system that is responsive to the evolving dynamics of digital transformation.